PENGARUH LATIHAN PLYOMETRIC (DOUBLE LEG BOUND) TERHADAP POWER OTOT TUNGKAI PADA TEAM PUTRA EKSTRAKURIKULER FUTSAL SMA DHARMA LOKA PEKANBARU - Devi Fernandez P; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted to determine whether there is influence of plyometric training (Double Leg Bound) to power the leg muscles High School futsal team ekstarkurikuler son Loka Dharma Pekanbaru, so that samples can maximize the results of kicks and defense. Research is a form of experiment, the population in this study is the son of extracurricular futsal team SMA Dharma Loka Pekanbaru. Sample in this research is the High School futsal team Loka Dharma Pekanbaru and amounted to 8 people. A sampling technique that is the overall total sampling son. The instruments used in this research is the Standing Broad Jump test, which aims to measure limb muscle power futsal team extracurricular high school son Loka Dharma. After that, if the statistical data, to test for normality with lilifors test at significant level 0,05α. The hypothesis is the influence of exercise Bound Double Leg to leg muscle power futsal team extracurricular high school son Loka Dharma Pekanbaru. Based on the analysis of statistical data, there are an average Pree-test amounted to 1.775 and the average post-test of 2,063, then the data is normal. Based on the analysis of the t test produces Thitung Ttabel 3.625 and 1.895, meaning Thitung> Ttabel. Thus, there Effect of Plyometric Exercises (Double Leg Bound) to power the leg muscles High School futsal team ekstarkurikuler son Loka Dharma Pekanbaru